The Relationship Between Self-Efficacy and Interpersonal Communication of Students of SMK Negeri 9 Padang - Lastri Werdani Sageileppak (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study is motivated by the existence of students who have low self-efficacy and interpersonal communication because they come from children of divorce victims, the purpose of this study is to determine the relationship between efficacy and interpersonal communication of broken home students of SMK Negeri 9 Padang. The type of research used in this study is quantitative with correlational research type. The study population amounted to 449 people, with a sample of 88 people taken using purposive sampling technique, the instrument used in data collection in this study was a questionnaire arranged according to the Likert scale model. Data analysis was carried out using a statistical program on the SPSS 20 computer and Microsoft excel. Based on the results of the hypothesis, the value of r count is 0.651 while the value of r table is 0.207 because r count is greater than r table (0.651>0.207), there is a relationship between self-efficacy and interpersonal communication of broken home students of SMK Negeri 9 Padang.